HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL YOUTUBE DENGAN KARAKTER RELIGIUS SISWA SMAN 10 KOTA BOGOR - Milatun Qoyimah (KOLONI, 2022)
The use of YouTube Social Media has various levels of intensity in using YouTube social media. Therefore, this study is to measure the relationship between the intensity of the use of YouTube social media and the religious character of the students of SMAN 10 Bogor City. Because the higher the intensity of the use of social media youTube is expected to increase the religious attitude of the students of SMAN 10 Bogor City. This study aims to determine the intensity of the use of YouTube social media, the religious character of the students, there is a significant relationship between the intensity of the use of YouTube social media and the religious character of the students, and how much influence the intensity of the use of YouTube social media has on the religious character of the students of SMAN 10 Bogor City. This study uses a quantitative approach with the correlational method. The data collection technique used is a questionnaire. The results showed that the intensity of the use of YouTube social media (58.60%) was in the medium category, religious characters (79.82%) were in the high category. 0.07%) is influenced by other variables not examined. While the t-count value obtained from the calculation results is 8.376 with a significant value of 0.000 which is smaller than the 5% error level and the t-table is 1.984, in this case t-count > t-table is 8.376 > 2.017, it shows that there is a relationship between the Intensity of Social Media Use YouTube on the Religious Character variable. Keywords: Intensity, Religious Character, High School Students.